Analysis of the Participation Level of DPRD Members in the Decision-Making Process: A Case Study of the DPRD of Tual City, Maluku Province - Fitri Rahmi A. Rahman; Risma Niswaty; Herman H; Dian Meliani Yulis (Universitas Negeri Makassar, 2025)
Indonesia adheres to the Pancasila Democracy system, where sovereignty lies in the hands of the people. In this system, the people have the right to elect their representatives through general elections, who are tasked with voicing and protecting the interests of the people in various aspects of government. This principle is translated into regional autonomy, which gives authority to local governments to regulate and manage their own government affairs in their regions. Regional autonomy is a form of decentralization designed to bring the government closer to the people, ensuring that the policies and decisions taken are more in line with local needs and conditions. There are three main pillars that support regional autonomy: (1) sharing of power, (2) distribution of income, and (3) independence or empowerment of local governments. The Regional People's Representative Council (DPRD), as part of the regional government structure, has an important role in carrying out legislative, budgeting, and oversight functions, all of which are rooted in the principles of autonomy. The study aims to determine the level of participation of DPRD members in the decision-making process in the DPRD of Tual City, Maluku Province and to examine the factors that influence the participation of DPRD members in decision-making in the DPRD of Tual City, Maluku Province. This type of research is descriptive qualitative research with data collection techniques, namely interviews, observations, and documentation. The checking of data validity is carried out through source triangulation. Data analysis techniques use data condensation, data presentation, and drawing conclusions. The results of the study indicate that political pressure, especially from external parties such as the community and certain figures, often influences the independence of members in decision-making. In addition, party interests have a dominant role that makes members prioritize loyalty to the party over the needs of the local community. Party motivation, although providing a clear framework, often limits individual freedom of movement. Leadership dominance was also found to reduce the diversity of perspectives in strategic meetings. Meanwhile, the lack of coordination between members and between leaders and staff hinders efficient decision-making. This study concludes that in order to increase the active participation of DPRD members, efforts are needed to minimize external political pressure, balance party interests with community needs, and improve internal coordination mechanisms. This research is expected to provide input for the DPRD and policy makers in increasing the effectiveness of democratic governance.